Phase I/II study of pralatrexate in Japanese patients with relapsed or refractory peripheral T‐cell lymphoma. Issue 10 (4th September 2017) - Maruyama, Dai; Nagai, Hirokazu; Maeda, Yoshinobu; Nakane, Takahiko; Shimoyama, Tatsu; Nakazato, Tomonori; Sakai, Rika; Ishikawa, Takayuki; Izutsu, Koji; Ueda, Ryuzo; Tobinai, Kensei
Abstract : Pralatrexate is a novel antifolate approved in the USA for the treatment of relapsed or refractory peripheral T‐cell lymphoma. To assess its safety, efficacy, and pharmacokinetics in Japanese patients with this disease, we undertook a phase I/II study. Pralatrexate was given i.v. weekly for 6 weeks of a 7‐week cycle. All patients received concurrent vitamin B12 and folic acid. In phase I, three patients received pralatrexate 30 mg/m 2 and none experienced a dose‐limiting toxicity. In phase II, we treated 22 additional patients with that dose. The median number of treatment cycles was 1 (range, 1–9). Nine of 20 evaluable patients (45%) achieved an objective response by central review, including two complete responses. All responses occurred within the first treatment cycle. At the time of data cut‐off, median progression‐free survival was 150 days. Median overall survival was not reached. In the total population, the most commonly reported adverse events included mucositis (88%), thrombocytopenia (68%), liver function test abnormality (64%), anemia (60%), and lymphopenia (56%). Grade 3/4 adverse events included lymphopenia (52%), thrombocytopenia (40%), leukopenia (28%), neutropenia (24%), anemia (20%), and mucositis (20%). The pharmacokinetic profile showed no drug accumulation with repeat dosing. These results indicate that pralatrexate is generally well tolerated and effective in Japanese patients with relapsed or refractory peripheral T‐cell lymphoma. This trial was registered with ClinicalTrials.gov (NCT02013362). Abstract : A phase I/II study of novel antifolate pralatrexate was conducted in 25 Japanese patients with relapsed or refractory peripheral T‐cell lymphoma. Results demonstrated a 45% objective response by central review (9 of 20 evaluable patients), including two complete responses, median duration of response not reached, median progression‐free survival of 150 days, median overall survival not reached, and grade 3‐4 toxicities as follows: 52% lymphopenia, 40% thrombocytopenia, 28% leukopenia, 24% neutropenia, 20% anemia, 20% mucositis.